Increasing Public Awareness About the Use of Masks and Antiseptics in Efforts to Prevent the Transmission of Covid-19 - Galih Abdul Fatah Maulani; Fikri Gumelar; Herni Nur Rohmah; Puja Alasmana; Tiara Nurul Muqsitu (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract Covid-19 is a pandemic that has occurred in various parts of the world and has become a form of public concern. The transmission of this disease can be prevented by using a mask and maintaining cleanliness, one of which is by using an antiseptic. Antiseptic is a substance that can destroy microorganisms in living tissue. The use of a good mask is to use 3 layers of cotton. The purpose of this study is to increase public awareness about the use of masks and antiseptics in preventing transmission of the corona virus for residents who will participate in activities by getting used to washing hands, using masks and antiseptics when doing activities. The method of implementing this activity is by conducting a field survey, especially in Paas Village, starting from the distribution of masks and antiseptics to the targets which are divided into several places, namely Posyandu, Ath-Thoyyibah Mosque, Independent tutoring place, then carrying out health protocol activities for the community. By carrying out the distribution of masks and antiseptics, people who especially do not wear masks are helped to get PPE and wash their hands frequently to prevent the Covid-19 virus. Abstrak Covid-19 merupakan pandemi yang terjadi di berbagai belahan dunia dan menjadi salah satu bentuk kekhawatiran masyarakat. Penularan penyakit ini dapat dicegah dengan menggunakan masker dan menjaga kebersihan salah satunya dengan menggunakan antiseptik. Antiseptik adalah zat yang dapat menghancurkan mikroorganisme pada jaringan hidup. Penggunaan masker yang baik yaitu dengan menggunakan 3 lapis berbahan katun. Tujuan penelitian ini adalah untuk meningkatkan kesadaran masyarakat tentang penggunaan masker dan antiseptic dalam mencegah penularan virus corona bagi warga yang akan mengikuti kegiatan dengan cara membiasakan mencuci tangan, menggunakan masker dan antiseptic saat akan melakukan aktivitas. Metode pelaksanaan kegiatan ini dengan melakukan survei lapangan khususnya di Desa Paas, dimulai dari pembagian masker dan antiseptic kepada sasaran yang dibagi menjadi beberapa tempat yaitu Posyandu, Masjid Ath-Thoyyibah, Tempat les mandiri, selanjutnya dilakukan kegiatan protokol kesehatan kepada masyarakat. Dengan dilaksanakannya pembagian masker dan Antiseptic ini masyarakat yang khususnya tidak memakai masker ini menjadi terbantu mendapatkan APD dan sering mencuci tangan untuk pencegahan dari virus Covid-19.